2012
DOI: 10.1007/s12975-012-0166-9
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Reduces Neuroinflammation and Transsynaptic Neuronal Apoptosis in a Model of Subarachnoid Hemorrhage

Abstract: Subarachnoid hemorrhage (SAH) can lead to disabling motor, cognitive, and neuropsychological abnormalities. Part of the secondary injury to cerebral tissues associated with SAH is attributable to the neuroinflammatory response induced by blood. Heparin is a pleiotropic compound that reduces inflammatory responses in conditions outside the central nervous system. Using a model of SAH devoid of global insult, we evaluated the effect of delayed intravenous (IV) infusion of heparin, at a dose that does not produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 83 publications
2
59
0
1
Order By: Relevance
“…Patients administered a low-dose intravenous heparin infusion within 48 hours of their ictus experienced significantly fewer occurrences of symptomatic vasospasm and infarcts compared with controls. The favorable results reported in this study, bolstered by strong physiological 60 and preclinical data, 61 suggest that a multicenter dose and safety assessment of intravenous heparin infusion (conventional unfractionated heparin, low-molecular-weight heparin, or nonanticoagulating N-desulfated heparin), 3,55 may be warranted.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Patients administered a low-dose intravenous heparin infusion within 48 hours of their ictus experienced significantly fewer occurrences of symptomatic vasospasm and infarcts compared with controls. The favorable results reported in this study, bolstered by strong physiological 60 and preclinical data, 61 suggest that a multicenter dose and safety assessment of intravenous heparin infusion (conventional unfractionated heparin, low-molecular-weight heparin, or nonanticoagulating N-desulfated heparin), 3,55 may be warranted.…”
Section: Discussionmentioning
confidence: 68%
“…50 Recent work has shown that low-dose intravenous heparin infusion significantly reduces neuroinflammation (neutrophils, activated phagocytic microglia, nuclear factor κB, tumor necrosis factor–α, and IL-1β) as well as transsynaptic apoptosis in a preclinical model of aSAH involving eloquent cortex. 61 To our knowledge, no other compound has been identified that exhibits such a broad diversity of biological effects that are so intimately relevant to mechanisms implicated in aSAH-induced DNDs. The very multiplicity of mechanisms targeted by heparin suggests that it may be useful as a multitargeted prophylactic agent to ameliorate the wide-ranging abnormalities induced by aSAH.…”
mentioning
confidence: 99%
“…Simard et al 16 showed in a rat SAH model that heparin treatment reduced neuroinflammation, demyelination, and neuronal apoptosis, indicating a reduction of adverse effects in SAH. Furthermore, Altay et al 29 recently showed improvement in neurobehavioral function and a decrease in brain edema in mice pretreated with low-dose unfractionated heparin before SAH induction.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we focused on the anti-apoptotic mechanisms of CB2R stimulation. However, other potential mechanisms of CB2R stimulation could play a role in providing beneficial effect after SAH, which we did not explore in this study (Simard et al, 2012). This might be a possible explanation as to why we did not observe statistically significant neurological deterioration in SAH rats that received CREB siRNA injection as opposed to control siRNA, since anti-apotosis may be one of the many protective mechanisms of CB2R agonist induced neuroprotection.…”
Section: Discussionmentioning
confidence: 94%